Réflexions autour de la notion de vraisemblance dans l’art du portrait royal à la Renaissance : l’exemple des représentations du souverain Henri IV - Juliette Souperbie (Les Cahiers de Framespa)
Illustrious people’s portraits, whilst having gained the aura of historical documents or even authentic archives, remain imagined creations that reveal only partly the truth. The calling of a political portrait has always been to convey positive and beneficial messages. Having become a powerful communication tool in the Renaissance, it subtly associated real elements with strategies of representation praising the leader’s virtues. Henry IV was a king who encountered great difficulties in establishing his power, but he knew how to use his image to respond to disputes and legitimize his position on the throne of France. This article initiates a dialogue between the existing historiography on royal portraits and an analysis of portraits of Henry IV created between 1600 and 1610 in order to question the limits of authenticity in the study of this type of representation.